Next-Generation CPU Architectures: A Study of the Influence of Nanometer Technology on Computer Performance - Ija Sudija; Jan everhard riwurohi; Muhamad Masruin Masad (Eduvest - Journal of Universal Studies, 2024)
Nanometer technology has become one of the most significant innovations in the advancement of modern CPU architecture, enabling substantial improvements in computational performance, energy efficiency, and transistor density. This study examines the impact of 7nm, 5nm, and 3nm technology implementation on CPU performance under various workload scenarios, including multitasking, graphics rendering, and artificial intelligence-based applications. Based on a series of experimental tests, the findings indicate that reducing transistor size directly increases processor speed by up to 30% while reducing power consumption by 20%. However, challenges such as heat dissipation and power leakage become more pronounced with technology below 5nm. Several proposed solutions include the development of more advanced cooling systems and the use of alternative semiconductor materials, such as graphene, to mitigate power leakage. This research provides valuable insights into the future development of CPU architecture and its impact on the technology industry as a whole.